(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Because the big grown of the digital market and the growing demand for protection to data and information which transmitted through the Internet. Steganography is the art of embedding, hiding information into different digital media, it was the main reason to increase its importance in the exponential development of the secret communication of computer and digital cloud users over the internet. There are a lot of techniques and different ways to achieve hiding data. Usually, the data embedding is obtained in communication such as image, text, voice or any multimedia content for copyright and also in military communication for authentication and many other different purposes. In this paper, we protected the information in two ways: Encryption and Steganography. The basic idea is to present a method that encrypted the message firstly by using The AES (Advanced Encryption Standard) it is a symmetric-key encryption each of these ciphers it has 128-bit the size to block, and size keys of 128, 192 and 256 bits. Secondly, hide that encrypted message in color cover image in the Least Significant Bit (LSB) to image’s frame with (.bmp, .jpg) extensions. Our scheme is to enhance the ability of LSB algorithm to include the storage of information and images encoded and intangible sense of human vision. That two methods to increased together the security attend any attack.